2014
DOI: 10.1177/1049909114537110
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine as a Tool to Provide Family Conferences and Palliative Care Consultations in Critically Ill Patients at Rural Health Care Institutions

Abstract: This study demonstrates that palliative care consultations can be provided via telemedicine for critically ill patients and that adequate preparation and technical expertise are essential. Although this study is limited by the nature of the retrospective review, it is evident that more research is needed to further assess its applicability, utility, and acceptability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 17 publications
0
36
0
Order By: Relevance
“…[1][2][3] Telehealth in its many forms offers conveniences including increased care accessibility, decreased transportation barriers, and patient empowerment. [4][5][6][7][8] Studies of video visits have demonstrated these benefits in specialty settings including wound care, prenatal genetic screening, family planning, cardiovascular care, and home care. [9][10][11][12][13][14][15] One study of patient experiences with video visits in rural areas found that they were associated with decreased travel costs and lost time/wages, increased access to social support, and better ability to tailor care delivery to patient and family needs.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Telehealth in its many forms offers conveniences including increased care accessibility, decreased transportation barriers, and patient empowerment. [4][5][6][7][8] Studies of video visits have demonstrated these benefits in specialty settings including wound care, prenatal genetic screening, family planning, cardiovascular care, and home care. [9][10][11][12][13][14][15] One study of patient experiences with video visits in rural areas found that they were associated with decreased travel costs and lost time/wages, increased access to social support, and better ability to tailor care delivery to patient and family needs.…”
Section: Introductionmentioning
confidence: 99%
“…The quantitative studies all used a cross‐sectional descriptive design and were conducted in the United States . As part of a quality improvement initiative, Brown et al used a closed‐ended survey‐styled questionnaire to evaluate the family members' perceptions of accompanying a critically ill relative during air transport to an urban tertiary care centre.…”
Section: Resultsmentioning
confidence: 99%
“…However, because the findings by Brown et al align with previously described methodologically sound studies, this study was included in the development of this integrative review. Menon et al completed a small retrospective chart review to determine the feasibility of using telemedicine family conferences to support rural family members during a relative's IFT. Although this study is methodologically sound in addressing the study aim, data from family participants were not collected.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of telemedicine in NHs have evaluated the use of technology to improve access to services such palliative care through remote consults, 45 teledermatology, 46-50 telepsychiatry 51-55 and potentially other specialties such as cardiology, pulmonary and neurology. Thus, telemedicine could be leveraged more broadly as a platform for providing other services, such as enhanced access to other specialty care, elevating the technology to a ‘horizontal,’ cross-cutting intervention within a NH and potentially increasing the associated clinical and financial benefits.…”
Section: Discussionmentioning
confidence: 99%